The Effectiveness of Providing Health Education on Mother's Knowledge and Interests About Integrated healthcare center Toddlers In Parakan Village, Trenggalek District, Trenggalek Regency - Gesytra Asmeranda Cahyaning Ciputri; Shanty Natalia (Open Access Health Scientific Journal, 2021)
Background: The function of the toddler integrated healthcare center is important in monitoring the growth and development of children, but there are still many mothers of toddlers who do not regularly visit the integrated healthcare center. This can be influenced by various factors, including the low level of knowledge and interest of mothers in integrated healthcare center. Method: The design of this study was pre-experimental with a one-group pre-post test approach. The population of all mothers of toddlers aged 3-5 years in Parakan Village amounted to 132 people, with a probability sampling technique obtained a sample of 33 respondents. The independent variable of health education with the dependent variable of knowledge and interest, the results were analyzed by the Wilcoxon signed rank test at = 0.05. Results: The results showed that most of the respondents prior to receiving health education had sufficient knowledge category, namely 20 respondents (60.6%) and had moderate interest category, namely 18 respondents (54.5%). After health education, it was known that almost all respondents had good knowledge, namely 27 respondents (81.8%) and most of them had high interest categories, namely 21 respondents (63.6%). Conclusion: The provision of information stimulus can increase knowledge and trigger interest in making regular visits so that it is hoped that there will be ongoing health education activities to maintain maternal visits to integrated healthcare center